Profil Pendugaan Senyawa Volatil Hasil Fermentasi Whey Keju yang Berpotensi sebagai Flavor - Dimawarnita, Firda; Kusuma, Azzakiyya Salsabila Syifa; Perwitasari, Urip; Zubaidah, Elok; Faramitha, Yora; Juanssilfero, Ario Betha (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2025)
Cheese whey, as a by product of cheese processing, contains high levels of protein and lactose, which can be utilized as a substitute medium for the growth of lactic acid bacteria (LAB) to produce flavor compounds, thereby enhancing its economic value. This study aims to identify the volatile flavor compounds present in the product resulting from de Man Rogosa and Sharpe Broth (MRSB) media with partial substitution of cheese whey (5, 15, and 30% v/v) as a source of carbon and nitrogen. The analysis was carried out using gas chromatography-mass spectrometry (GC-MS) while other observed parameters included pH, total acid, and carbon nitrogen content. The results of the study showed that the substitution of cheese whey at 5% showed the best results, and produced bioflavor compounds such as 2(5H)-furanone (almond) and benzenacetaldehyde (rose) with pH 4.57±0.012, total acid 0.88%, total carbon 15.86±0.292%, and total nitrogen 1.39±0.177%. These findings indicate that cheese whey can serve as an effective substitute for carbon and nitrogen sources in growth media to produce volatile compounds with potential flavor properties by Lactobacillus sp.